Choosing a Mouse Model of Venous Thrombosis: A Consensus Assessment of Utility and Application. Issue 3 (March 2019) - Diaz, Jose A.; Saha, Prakash; Cooley, Brian; Palmer, Olivia R.; Grover, Steven P.; Mackman, Nigel; Wakefield, Thomas W.; Henke, Peter K.; Smith, Alberto; Lal, Brajesh K.
Abstract : Murine models are widely used valuable tools to study deep vein thrombosis. Leading experts in venous thrombosis research came together through the American Venous Forum to develop a consensus on maximizing the utility and application of available mouse models of venous thrombosis. In this work, we provide an algorithm for model selection, with discussion of the advantages, disadvantages, and applications of the main mouse models of venous thrombosis. Additionally, we provide a detailed surgical description of the models with guidelines to validate surgical technique. Abstract : Supplemental Digital Content is available in the text.